La cultura tributaria y su incidencia en la recaudación de impuestos. caso Machala, provincia El Oro, periodo 2015 - 2019. - Macas Iñaguazo, María José (My University, 2021)
Tax Culture plays an important role in the collection of tax payments, because it allows guiding and fulfilling its obligations in an orderly, clear and voluntary manner. The objective of this study is to determine the economic activities that generate greater economic activity and higher tax generation in the city of Machala, Province of El Oro. The research presents a comparative descriptive approach, and the data collection was obtained from historical reports of the Service Internal Revenue. The main results were based on four parameters: first; analysis of income from tax collection concepts, second; analysis of the main taxes that generate the greatest contribution, third: classification of the main cities with the highest collection at the provincial level and fourth: analysis of the economic activities that generate the greatest contribution in the city of Machala. It is concluded that the income tax with 54.85% and the value added tax (VAT) with 30.07% are those taxes with the highest total collection in the city of Machala, in addition, its main economic activities are in Agriculture, forestry and fishing; Trade; Construction and Manufacturing, ranking the canton in first place as the largest collector in the province of El Oro.
La Cultura tributaria cumple un rol importante en la recaudación de pagos de impuestos, debido a que permite orientar y cumplir con sus obligaciones de forma ordenada, clara y voluntaria. Este estudio tiene como objetivo determinar las actividades económicas que generan mayor actividad económica y mayor generación de impuestos en la ciudad de Machala, Provincia de El Oro. La investigación presenta un enfoque descriptivo comparativo, y la recopilación de datos fue obtenida de informes históricos del Servicio de Rentas Internas. Los principales resultados se basaron en cuatro parámetros: primero; análisis de los ingresos por conceptos de recaudación de impuestos, segundo; análisis de los principales impuestos que generan mayor contribución, tercero: clasificación de las principales ciudades con mayor recaudación a nivel provincial y cuarto: análisis de las actividades económicas que generan mayor contribución en la ciudad de Machala. Se concluye que el impuesto a la renta con 54,85% y el impuesto al valor agregado (IVA) con 30,07% son aquellos tributos con mayor recaudación total en la ciudad de Machala, además que, sus principales actividades económicas se encuentran en Agricultura, ganadería, silvicultura y pesca; Comercio; Construcción y Manufactura, ubicándose el cantón en primer lugar como mayor recaudador en la provincia de El Oro.
Keywords: IMPUESTOS; RECAUDACIÓN